2016
DOI: 10.1063/1.4967238
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric backscattering from the hybrid magneto-electric meta particle

Abstract: Abstract:The optical theorem relates the total scattering cross-section of a given structure with its forward scattering, but does not impose any restrictions on other directions. Strong backward-forward asymmetry in scattering could be achieved by exploring retarded coupling between particles, exhibiting both electric and magnetic resonances. Here, a hybrid magneto-electric particle (HMEP), consisting of a split ring resonator acting as a magnetic dipole and a wire antenna acting as an electric dipole, is sho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…In order to demonstrate this effect, a scatterer, which electromagnetic analysis requires at least two leading dipole terms in the multipolar decomposition will be considered. While two dissimilar electric dipoles, separated by a wavelengthcomparable distance could possess asymmetric back scattering, being illuminated from opposite sides, combination of electric and magnetic dipoles was recently shown to provide an ultimate degree of asymmetry [10]. The hybrid magneto-electric particle (HMEP) consists of a SRR and a thin wire ( Fig.…”
Section: Theoretical Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to demonstrate this effect, a scatterer, which electromagnetic analysis requires at least two leading dipole terms in the multipolar decomposition will be considered. While two dissimilar electric dipoles, separated by a wavelengthcomparable distance could possess asymmetric back scattering, being illuminated from opposite sides, combination of electric and magnetic dipoles was recently shown to provide an ultimate degree of asymmetry [10]. The hybrid magneto-electric particle (HMEP) consists of a SRR and a thin wire ( Fig.…”
Section: Theoretical Formulationmentioning
confidence: 99%
“…In principle, a HMEP made of a pair of isotropic ED and MD, will show a similar micro-Doppler behavior to the one discussed hereafter. Adiabatic theory is based on the matrix formulation [10] and polarizability tensors, taken from Eq. 1.…”
Section: Adiabatic Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Individual and arrayed bianisotropic metamolecules have been designed and fabricated using a variety of material platforms, both dielectric and metallic, across a wide spectral range, from centimeters to nanometers [ 4,28,29,30,31,32,33,34,35]. While the interference between in-plane electric and magnetic resonances excited by a normally incident electromagnetic wave can introduce the up-down (forward/backward) scattering asymmetry, it has recently been shown that bianisotropic coupling between in-plane electric and out-of-plane magnetic moments can induce strong lateral scattering asymmetry [ 28,36] by a single metamolecule.…”
Section: Introductionmentioning
confidence: 99%
“…Except for a certain interest for mathematical physics, the analytical solutions may serve for description of structural anisotropy of metamaterials (see recent Refs. [37,38]), caused by the anisotropy of individual meta-atoms but not the lattice. In this case, the multipolar moments of these meta-atoms determine the properties of the whole metamaterial.…”
mentioning
confidence: 99%